The over-under on container networking (O'Reilly Media, 2017)
"Networking is an inherent component to any distributed application and one of the most complicated and expansive technologies central to microservices. With application developers busily adopting container technologies, the time has come for network engineers and operators to prepare for the unique challenges brought on by cloud-native applications. Lee Calcote walks you through available container connectivity options, explaining their function and when they should be used and comparing their performance characteristics."--Resource description page